REDESIGNING THE VISUAL IDENTITY OF KONKOU STUDIO AND ITS APPLICATION IN PROMOTIONAL MEDIA - Harris, Abdul Rafi Muhshi; Sugiarto, Eko (LPPM Univ. Ibn Khaldun Bogor, 2025)
In today's rapidly growing creative industry, a strong visual identity is essential for a studio to survive and compete professionally. This study aims to redesign the visual identity of Konkou Studio, a creative studio that was once active in the fields of design and branding but faced various internal issues such as conflicting visions and the absence of a strong organizational structure. The design process was conducted qualitatively using an exploratory approach through brainstorming and visual testing. The tools used include Procreate for initial illustrations and Adobe Illustrator for vector based designs. The design outcomes include a new logo, color system, and typography, as well as their application across various promotional media such as business cards, social media, websites, and merchandise. The evaluation indicates that the new design reflects the studio's professional and creative character and can be consistently applied across various platforms. This research underscores the importance of a well-defined visual identity and effective internal team management in supporting the sustainability of a creative studio. Keywords: Visual Identity, Creative Studio, Promotional Media